Financial Management of University Students: A Christian Faith Perspective - Betrand Pandiangan; Elsa Pronika Simanjuntak; Sintikhe Widya Jelita Tarigan; Talenta N. D. Simatupang (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Financial management is an essential skill for university students, particularly during their academic years when they face diverse academic and social demands. Students often rely on limited sources of income such as parental support, scholarships, or part-time work, while their expenses include basic needs, transportation, academic costs, leisure, and spiritual commitments. Within the Christian faith, finances are regarded as blessings from God that must be managed responsibly (stewardship), so that every financial decision reflects faithfulness and gratitude to Him (Luke 16:10; Philippians 4:11â€“12). In reality, many students lack adequate financial literacy, which leads to difficulties in balancing income and expenses. This challenge is further compounded by the influence of consumerist lifestyles and the absence of consistent budgeting practices. The purpose of this research is to provide an overview of studentsâ€™ financial management practices, highlight the challenges they encounter, and propose an innovative idea in the form of the â€œ3Pâ€ budgeting model (Personal, Ministry, Offering).